Developing a gymnastics-based fundamental movement model to enhance motor development in elementary school students - Christina Fajar Sriwahyuniati; Ahmad Nasrulloh; Cerika Rismayanthi; Hedi Ardiyanto Hermawan; Dhedhy Yuliawan (Universitas Nusantara PGRI Kediri, 2025)
This study aims to develop an engaging and innovative fundamental gymnastics movement model for elementary school students in Phases A (ages 6–8) and B (ages 8–10), with an emphasis on safety and practical applicability. Using the ADDIE development framework, Analysis, Design, Development, Implementation, and Evaluation, the research followed a Research and Development (R&D) approach. Expert validation was carried out by seven raters, consisting of five media experts and two gymnastics and fitness specialists, and their assessments were analyzed using Aiken's V. Product trials were conducted on a small scale at the UNY sports laboratory school (3 participants) and on a large scale at Pakem State Elementary School (8 participants). The model demonstrated strong feasibility, validity, and reliability, with an average expert judgment score of 89.46%. Content validity ranged from high to very high (V = 0.762–0.952), and internal consistency reliability was excellent (Cronbach’s α = 0.890). Trial results were also positive, increasing from 93.33% in the small-scale trial to 95.93% in the large-scale trial, reflecting a 2.6% improvement in practicality. These findings indicate that the developed gymnastics-based fundamental movement model can serve as an effective instructional tool in Physical Education, Sports, and Health (PJOK), supporting motor development and increasing learning engagement among young learners.